PENGEMBANGAN FILM ANIMASI BERBANTUAN ADOBE EXPRESS MATERI METAMORFOSIS PERUBAHAN BENTUK MAKHLUK HIDUP - Rahmawati Setia Ningrum; Tustiyana Windiyani; Suci Siti Lathifah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research aims to develop an Animation Film assisted by Adobe Express for third-grade students of SDN Bojonggede 01 and to determine the feasibility and effectiveness of animation films on the learning process conducted at school. The method in this research uses the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results showed that the development of animation films assisted by Adobe Express has feasibility and effectiveness to be applied in the learning process. This can be seen from the validation test results conducted by media experts, material experts, and language experts, obtaining an average score of 96% with very feasible criteria. The results of the student response questionnaire obtained 98%, the teacher response results were 96%, meaning that the responses of students and teachers received very feasible criteria, and the average N-Gain value of learning outcomes was 0.90 with an N-Gain Percentage of 90.51% with high criteria. Therefore, these results indicate that Animation Films assisted by Adobe Express are very feasible to use in the learning process and are very effective in improving student learning outcomes.